Lipid profile is similar in both subjects with high 1-hour postload glucose and 2-hour postload glucose and is related to cardio-metabolic profile in prediabetes - Dimova, Rumyana; Chakarova, Nevena; Serdarova, Mina; Tankova, Tsvetalina (Journal of diabetes and its complications, 2024)
The study aimed to investigate a lipid profile in people with normal glucose tolerance (NGT), NGT and 1hrOGTT > 8.6 mmol/l, and impaired glucose tolerance (IGT); and to assess its association with some cardio-metabolic parameters. A total of 90 subjects, of mean age 46.7 ± 10.5 years and mean BMI of 32.0 ± 6.3 kg/m2 were enrolled. They were divided into 3 groups: 19 with NGT, 22 with NGT and 1hrOGTT > 8.6 mmol/l, and 49 with IGT; and subdivided into 2 subgroups according to HOMA-IR: 40 with HOMA-IR < 2.5 and 50 with HOMA-IR ≥ 2.5. Body composition (Inbody 720) and advanced glycation end products (AGE Reader) were assessed. Two functional tests (OGTT; MMTT) were performed and AUC for glucose, insulin and triglycerides were calculated. There was no difference across the glucose tolerance groups for all evaluated lipids. The results showed higher AUCinsulin during OGTT (p = 0.037 and 0.020), AUCtriglycerides during MMTT (p = 0.048) and triglycerides/HDL ratio (p = 0.064 and 0.016) in the 1hrOGTT and IGT subgroups with HOMA-IR ≥ 2.5 in comparison to those with HOMA-IR < 2.5. AUCtriglycerides during OGTT is independently related to body composition, b-cell function and insulin sensitivity; and AUCtriglycerides during MMTT is independently related to blood pressure and hsCRP in prediabetes. Triglycerides/HDL-C ratio emerged as an independent contributor to glycaemia and insulinemia. Our results demonstrate a similar lipid profile in subjects with 1hrOGTT > 8.6 mmol/l and IGT, whereas increased AUCtriglycerides during OGTT, AUCtriglycerides during MMTT and triglycerides/HDL-C ratio have been found in the subgroups with insulin resistance. The triglycerides/HDL-C ratio outlined as an independent predictor of insulin secretion and action, and postload triglycerides appear to be independently related to most of the metabolic parameters. •The manuscript examines various prediabetes categories, including the newly adopted with high 1-hour post-load glucose.•The manuscript explores key lipid parameters including postprandial triglycerides that has been largely neglected to date.•The triglycerides/HDL ratio outlines as an independent predictor of basal and stimulated insulin secretion and sensitivity.•AUC for postprandial triglycerides is independently related to most of the traditional metabolic parameters in prediabetes.